The influence of media scrutiny on firms' strategic eschewal of lobbying - Kim, Jinsil; Welbourne Eleazar, Miranda J.; Lee, Seung‐Hyun (Strategic Management Journal, 2024)
Abstract Research Summary Lobbying allows firms to influence the government to potentially limit firms' costs during product recall crises. However, such lobbying can elicit scrutiny from the media if the lobbying gives the impression that firms wish to save costs at the expense of safety, thereby appearing hypocritical. We theorize that when faced with negative media coverage of product recalls or recall‐related lobbying, firms strategically eschew lobbying to limit further media scrutiny and its associated negative consequences. We test our hypotheses using the US auto industry's lobbying from 2008 to 2022. We provide further depth to our examination of strategic eschewal through 15 supplemental interviews of lobbyists about how the media influences firms' lobbying decisions. Managerial Summary Companies may resort to lobbying in efforts to reduce costs related to product recall crises, but such controversial lobbying may also tarnish their image. When confronted with negative media coverage of product recalls, or recall‐related lobbying, companies are more likely to strategically refrain from lobbying to minimize additional, unwanted media spotlight and its associated negative repercussions. Managers should be mindful that even if lobbying may help limit the costs of recalls, it could also cause potential reputational harm. Thus, it is vitally important that managers pay attention to the reputational cues from the media, which can help them determine when lobbying may be problematic and allow them to preemptively refrain from such lobbying.